Self-curing eco-friendly acrylic emulsion resin composition, method for manufacturing the same, and elastic putty composition manufactured using the same
Patent Information
- Application Number
- KR1020260081615
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2026-05-06
- Publication Date
- 2026-09-15
- Estimated Expiration
- 2046-05-06
Smart Images

Figure 112026054742475-PAT00001 
Figure 112026054742475-PAT00002
Abstract
Description
Technology Field
[0001] The present invention relates to a self-curing eco-friendly acrylic emulsion resin composition, a method for manufacturing the same, and an elastic putty composition manufactured using the same. More specifically, the invention relates to an improved self-curing eco-friendly acrylic emulsion resin composition and a method for manufacturing the same, and an elastic putty composition manufactured using the same, which is based on a water-dispersible acrylic emulsion system that does not use organic solvents to secure excellent elongation, tensile strength, and adhesion, and includes a plasticizing system capable of gloss control using diatomaceous earth and maintaining physical properties even in low-temperature environments, thereby enabling the suppression of staining and the realization of a uniform matte surface even after topcoat painting when applied as an elastic putty for crack repair in concrete structures. Background Technology
[0002] In general, microcracks develop in concrete structures over time due to drying shrinkage, temperature changes, and external loads, and these cracks lead to a decrease in structural durability and leakage problems.
[0003] Accordingly, various types of putty and waterproofing paints are being used to fill cracks and ensure waterproofing performance.
[0004] Conventional water-based acrylic emulsion putties have advantages in terms of eco-friendliness, but they have a problem in that they cannot cope with the repeated expansion of cracks due to insufficient tensile strength and elongation.
[0005] In addition, standard acrylic putty causes the repaired area to appear stain-like due to differences in gloss after the topcoat, resulting in a decrease in aesthetic quality.
[0006] Meanwhile, solvent-based urethane or rubber-based waterproofing paints possess excellent elasticity and durability, but they pose a problem of adverse effects on workers' health and the environment due to the inclusion of volatile organic compounds (VOCs).
[0007] In addition, two-component systems have the disadvantage of requiring skill, as it is difficult to control the mixing ratio on-site, resulting in quality variations.
[0008] In addition, prior art registered patent No. 10-1405133 proposes a waterproof paint using a water-dispersible acrylic urethane emulsion, but as this is a paint-centered technology, it does not sufficiently solve issues such as gloss control when applying putty, maintaining flexibility at low temperatures, and the appearance of the topcoat after crack repair.
[0009] In particular, conventional technology has lacked the ability to simultaneously ensure construction convenience and physical property stability through an increase in the solid content of the putty itself and a self-curing mechanism.
[0010] In addition, there was a problem with reduced crack-following ability due to the rapid decrease in elongation in low-temperature winter environments.
[0011] Furthermore, existing putty compositions had a limitation in that it was difficult to control surface gloss after film formation, resulting in a visual discrepancy when applying a topcoat.
[0012] Therefore, a new acrylic emulsion-based putty technology is required that can simultaneously achieve high elongation, high tensile strength, low-temperature flexibility, and a matte surface while maintaining eco-friendliness. Prior art literature
[0013] Korean Registered Patent No. 10-1405133 The problem to be solved
[0014] The objective of the present invention is to provide a self-curing eco-friendly acrylic emulsion resin composition, an elastic putty composition using the same, and a method for manufacturing the same, which improves construction convenience by imparting self-curing characteristics based on an eco-friendly water-dispersible system that does not use organic solvents, simultaneously improves tensile strength and elongation through an increase in solid content, maintains crack-following properties even in low-temperature environments through gloss control using diatomaceous earth and the introduction of a plasticizer, and enables the realization of a uniform surface that does not stain even after topcoat painting. means of solving the problem
[0015] The present invention, as a means to achieve the above-mentioned objective, comprises 1.0-2.0 wt% diacetone acrylamide, 15-20 wt% n-butyl acrylate, 0.5-1.5 wt% methacrylic acid, 1.0-2.2 wt% acrylonitrile, 13-18 wt% butyl methacrylate, 13.2-17.5 wt% 2-ethylhexyl acrylate, 2.2-3.0 wt% styrene, 0.5-2.0 wt% adipic acid dihydrazide, 0.07-0.2 wt% ammonium peroxide, 0.06-2.2 wt% ammonium persulfate, 0.1-0.5 wt% ammonium hydroxide, 0.25-0.75 wt% nonionic emulsifier, and the remainder being ion-exchanged water, wherein by the reaction between the diacetone acrylamide and the adipic acid dihydrazide The present invention provides a self-curing eco-friendly acrylic emulsion resin composition characterized by forming a self-crosslinking structure, having a solid content of 60% by weight or more, a viscosity of 2900-3100 cps (25℃), and a glass transition temperature (Tg) of -23℃ to -25℃.
[0016] In addition, the present invention provides a method for manufacturing a self-curing eco-friendly acrylic emulsion resin composition, comprising: (a) a step of introducing an initiator into an aqueous reaction system containing ion-exchanged water and a nonionic emulsifier and initiating a reaction at 70 to 90°C; (b) a step of copolymerizing by drop-introducing a monomer mixture for 3 to 4 hours; (c) a step of performing secondary polymerization by introducing an additional initiator and removing unreacted monomers under vacuum; and (d) a step of cooling the reaction mixture to 40 to 50°C and then adjusting the pH to stabilize the emulsion.
[0017] In addition, the present invention comprises 55-65 wt% of the self-curing acrylic emulsion resin composition, 0.1-0.3 wt% sodium hexametaphosphate, 4.0-8.5 wt% water, 0.2-0.5 wt% 1,2-benzisothiazolin-3-one, 0.5-3.0 wt% TiO₂, 0.5-1.3 wt% hydroxyethyl cellulose, 1-6 wt% pigment, 0.1-0.3 wt% polydimethylsiloxane, 1-2 wt% DOA, 1.5-3.0 wt% Texanol, 10-15 wt% diatomite, 0.1-1.0 wt% hydrophobic modified urethane-based thickener, and the remainder being calcium carbonate, wherein the gloss of the coating film is reduced by the diatomite, thereby suppressing the occurrence of stains during topcoat application, and the low temperature by the DOA An elastic putty composition is provided that is characterized by maintaining elongation even in an environment. Effects of the invention
[0018] According to the present invention, the following effects can be obtained.
[0019] First, through the self-curing acrylic emulsion structure, a uniform film can be formed without mixing a separate curing agent, thereby improving workability.
[0020] Second, by designing an acrylic emulsion with a high solid content, tensile strength and elongation exceeding KS standards can be secured.
[0021] Third, by including diatomaceous earth, the gloss of the coating film is effectively controlled, thereby suppressing the occurrence of stains after topcoat application.
[0022] Fourth, by including DOA plasticizers, elongation can be maintained even in low-temperature environments.
[0023] Fifth, as an eco-friendly water dispersion system, it generates low levels of VOCs and is safe for the human body and the environment.
[0024] Sixth, long-term durability and waterproofing can be secured simultaneously when repairing concrete cracks. Specific details for implementing the invention
[0025] Hereinafter, preferred embodiments according to the present invention will be described in more detail.
[0026] The self-curing eco-friendly acrylic emulsion resin composition according to the present invention comprises 1.0 to 2.0 wt% diacetone acrylamide, 15 to 20 wt% n-butyl acrylate, 0.5 to 1.5 wt% methacrylic acid, 1.0 to 2.2 wt% acrylonitrile, 13 to 18 wt% butyl methacrylate, 13.2 to 17.5 wt% 2-ethylhexyl acrylate, 2.2 to 3.0 wt% styrene, 0.5 to 2.0 wt% adipic acid dihydrazide, 0.07 to 0.2 wt% ammonium peroxide, 0.06 to 2.2 wt% ammonium persulfate, 0.1 to 0.5 wt% ammonium hydroxide, 0.25 to 0.75 wt% nonionic emulsifier, and the remainder being ion-exchanged water.
[0027] At this time, when synthesizing the acrylic emulsion, it is desirable to maintain a solid content of 60% or more, and after the reaction, it is desirable to achieve a viscosity of 2900-3100 cps (25℃) and a glass transition temperature (Tg) of -23℃ to -25℃.
[0028] Here, maintaining a solid content of 60% or more has the advantage of allowing for a thicker coating when the same amount is applied and a faster drying speed.
[0029] In addition, viscosity refers to stickiness, or flow resistance; since it flows down if it is too thin and is difficult to spread thinly if it is too thick, it is best to maintain a viscosity of 2900-3100 cps, which has a syrup-like consistency at 25°C.
[0030] In particular, the fact that the Tg is low from -23℃ to -25℃ means that this material is very soft, flexible, and sticky (adhesive) at room temperature (about 20~25℃), so it is very suitable for making elastic putty because it does not harden or crack even in cold winters.
[0031] In addition, among the above compositions, diacetone acrylamide is a key functional monomer that reacts with adipic acid dihydrazide described later to form a self-crosslinking structure, and plays a role in improving the durability and water resistance of the coating film by forming a crosslinked structure within the coating film without an external curing agent.
[0032] In particular, if the content of the component is excessively low, it is difficult to secure sufficient crosslinking density, which degrades physical properties; conversely, if it is in excess, it can lead to reaction imbalance and reduced storage stability, so it is important to include it selectively within a certain range.
[0033] In addition, n-butyl acrylate and 2-ethylhexyl acrylate are soft monomers with a low glass transition temperature (Tg) that provide excellent flexibility and elongation to the coating film.
[0034] These soft monomers are essential to enable the coating to absorb deformation without cracking, particularly in response to the repeated expansion and contraction of concrete structures.
[0035] On the other hand, butyl methacrylate and styrene are monomers with relatively hard properties that improve the mechanical strength and wear resistance of the coating film, and a balance between strength and elasticity is secured through appropriate ratio control with soft monomers.
[0036] In addition, methacrylic acid introduces carboxyl groups during the copolymerization process to improve inter-particle stability and simultaneously increase adhesion to the substrate (concrete, etc.).
[0037] This acts as an important factor in ensuring that the coating film is firmly bonded to the substrate to maintain long-term durability.
[0038] In addition, acrylonitrile serves as a component to improve chemical and stain resistance, contributing to enhanced resistance to the external environment.
[0039] In addition, adipic acid dihydrazide is included as a curing component, and a self-curing structure is realized by reacting with the diacetone acrylamide to form a hydrazone bond.
[0040] This self-curing mechanism enables a one-component system that does not require a separate curing agent mixing process, thereby significantly improving construction convenience while ensuring uniform physical properties.
[0041] In addition, ammonium peroxide and ammonium persulfate act as radical initiators to initiate and promote polymerization reactions between monomers, and ammonium hydroxide plays a role in ensuring the stability of the emulsion by adjusting the pH after the reaction.
[0042] In addition, alcohol ethoxylate can be used as a nonionic emulsifier, which induces uniform dispersion of monomer particles to stabilize the size distribution of emulsion particles and consequently contributes to improving the uniformity of the coating film.
[0043] Finally, the ion-exchanged water acts as a reaction medium and ensures the reproducibility and stability of the polymerization reaction by maintaining a state free of impurities.
[0044] The acrylic emulsion resin manufactured in this way is designed to have a structure with a high solid content, which, as previously explained, plays an important role in improving filling and film-forming ability when applying putty, and in suppressing crack formation by minimizing shrinkage after drying.
[0045] In addition, the present invention may further add 5.5 parts by weight of 2-(acetoacetoxy)ethyl methacrylate, 5 parts by weight of trimethylolpropane tris(2-methyl-1-aziridinepropionate), and 4.5 parts by weight of perfluoropolyether methacrylate to 100 parts by weight of the self-curing eco-friendly acrylic emulsion resin composition.
[0046] In this case, 2-(acetoacetoxy)ethyl methacrylate forms a double crosslinking mechanism to dramatically increase adhesion to the metal substrate, suppress the peeling of the coating film especially in humid environments, and has the advantage of improving workability by finely controlling the crosslinking speed at room temperature and significantly enhancing the scratch resistance of the final coating film.
[0047] In addition, trimethylolpropane tris(2-methyl-1-aziridinepropionate) is a high-performance polyfunctional aziridine crosslinking agent that reacts strongly with carboxyl groups in aqueous emulsion systems even at very low temperatures and reacts with methacrylic acid in the composition to make the three-dimensional network structure denser, which has the advantage of significantly improving chemical resistance (solvent resistance) and water resistance.
[0048] In addition, perfluoropolyether methacrylate has the advantage of providing strong anti-fouling performance and water and oil repellency by drastically lowering the surface energy of the coating surface.
[0049] Meanwhile, the elastic putty composition according to the present invention further improves functional characteristics by including various additives with the acrylic emulsion resin as the main component.
[0050] An elastic putty composition using such a self-curing eco-friendly acrylic emulsion resin composition comprises 55-65 wt% of the acrylic emulsion resin composition, 0.1-0.3 wt% sodium hexametaphosphate, 4.0-8.5 wt% water, 0.2-0.5 wt% 1,2-benzisothiazolin-3-one, 0.5-3.0 wt% TiO2, 0.5-1.3 wt% hydroxyethyl cellulose, 1-6 wt% pigment, 0.1-0.3 wt% polydimethylsiloxane, 1-2 wt% DOA, 1.5-3.0 wt% Texanol, 10-15 wt% diatomaceous earth, and hydrophobic It consists of 0.1 to 1.0 weight percent of hydrophobically modified urethane and the remainder being calcium carbonate.
[0051] At this time, sodium hexametaphosphate plays a role in improving storage stability and the uniformity of the coating film by uniformly dispersing inorganic pigments and fillers such as calcium carbonate through electrical repulsion and preventing aggregation.
[0052] In addition, 1,2-benzisothiazolin-3-one inhibits the growth of bacteria and fungi in water-dispersible compositions, thereby ensuring long-term storage stability of the product and preventing spoilage and the occurrence of bad odors.
[0053] In addition, TiO2 performs the function of improving aesthetics by controlling the opacity and color of the coating film.
[0054] In addition, hydroxyethyl cellulose increases viscosity in water-based systems and controls flow characteristics to prevent sagging during application, and improves the workability and film uniformity of the putty.
[0055] In addition, known organic or inorganic pigments may be used.
[0056] Furthermore, polydimethylsiloxane effectively removes bubbles generated during the mixing and stirring process and suppresses re-foaming, thereby preventing the formation of pinholes and pores within the coating film.
[0057] In addition, DOA (dioctyl adipate) acts as a plasticizer to maintain the flexibility of the coating film even in low-temperature environments and prevents a decrease in crack-following ability during winter construction.
[0058] In addition, Texanol promotes the fusion of emulsion particles, enabling the formation of a stable film even at low temperatures.
[0059] In addition, diatomaceous earth is an inorganic material with a porous structure that induces fine diffuse reflection on the surface of the coating film to reduce gloss and prevents the putty area from being visually exposed during topcoat application, which is a key element in improving important problems that were not solved in conventional technology.
[0060] In addition, hydrophobically modified urethane thickeners control viscosity through physical interaction with resin particles and pigment particles, and impart shear thinning characteristics, thereby simultaneously improving workability and leveling.
[0061] Finally, calcium carbonate is responsible for forming the thickness of the coating and mechanical reinforcement, and plays an important role in ensuring the fillability as a putty.
[0062] In addition, the present invention may further add 8.5 parts by weight of γ-glycidoxypropyltrimethoxysilane, 3.5 parts by weight of polyetheramine, and 5 parts by weight of dimethylaminoethyl methacrylate to 100 parts by weight of the elastic putty composition.
[0063] At this time, γ-glycidoxypropyltrimethoxysilane chemically bonds between organic resin (acrylic) and inorganic filler (diatomite, calcium carbonate) to maximize interfacial adhesion, thereby dramatically increasing elasticity retention, and induces chemical bonding with concrete or cement substrates, contributing to preventing the putty from falling off even in humid environments.
[0064] In addition, polyetheramine acts as a reactive polymer dispersant to suppress pigment clumping or surface roughness, ensure flexibility of the coating film, and contribute to providing a buffering ability to absorb external shocks.
[0065] In addition, dimethylaminoethyl methacrylate is a functional monomer derivative that provides strong electrostatic adhesion and antibacterial and antifungal performance simultaneously. Since elastic putty is applied mainly to walls where moisture accumulates, it is susceptible to mold. In addition to general disinfectants (such as BIT), it provides antibacterial function to the polymer chain itself to increase durability. In particular, it forms an electrostatic attraction with the substrate surface having acidic groups, providing an excellent effect in improving initial wet adhesion, which adheres to the substrate immediately upon application.
[0066] On the other hand, the elastic putty composition according to the present invention is manufactured by first synthesizing a self-curing acrylic emulsion resin composition and then mixing various additives based thereon, and is configured such that, in particular, securing reaction stability during the emulsion polymerization step and ensuring dispersion uniformity and bubble removal during the putty manufacturing step have an important influence on the final physical properties.
[0067] Therefore, a method for preparing the acrylic emulsion resin composition of the present invention will be described first.
[0068] The acrylic emulsion resin composition according to the present invention is prepared by a water-based emulsion polymerization method in a reactor, wherein ion-exchanged water is introduced into the reactor and a non-ionic emulsifier is added thereto to form a system in which monomers can be stably dispersed.
[0069] Afterwards, a radical initiator such as ammonium peroxide is introduced as a polymerization initiator, and the internal temperature of the reactor is maintained in the range of about 70°C to 90°C.
[0070] This temperature range represents the optimal conditions for stably generating free radicals through the decomposition of the initiator while preventing excessive runaway reactions, and is essential for inducing a uniform initial polymerization reaction.
[0071] In the next step, a dropping process is performed in which a pre-composed monomer mixture is gradually introduced into the reactor over a period of time.
[0072] At this time, the monomer mixture is added continuously or intermittently over a period of about 3 to 4 hours. This drop-in method is intended to maintain a constant monomer concentration within the reactor, thereby preventing particle size non-uniformity and gel formation caused by rapid polymerization reactions, and to form an emulsion with a stable particle structure.
[0073] In particular, in a system in which various soft and hard monomers are mixed, as in the present invention, this drop process plays a very important role in ensuring the uniformity of copolymerization.
[0074] Next, after the first polymerization reaction is carried out, a reaction solution containing an additional initiator, such as ammonium persulfate, is added to induce an additional polymerization reaction, and a second polymerization is performed.
[0075] This step is intended to further react residual monomers that were not completely reacted in the first reaction, thereby improving the overall degree of polymerization and contributing to preventing the deterioration of physical properties caused by residual monomers during film formation.
[0076] In addition, after secondary polymerization, the reactor is maintained under vacuum for a certain period of time to remove unreacted monomers, thereby simultaneously ensuring the stability and eco-friendliness of the final resin.
[0077] After that, the reaction system is neutralized and stabilized by adding a pH adjuster such as ammonium hydroxide while gradually lowering the temperature of the reaction mixture to about 40°C to 50°C.
[0078] This post-processing step is intended to ensure the electrical stability of emulsion particles and prevent aggregation or precipitation during storage, and is a very important process in terms of ensuring the long-term stability of the final product.
[0079] The self-curing acrylic emulsion resin composition prepared in this manner is subsequently used in the step of manufacturing an elastic putty composition, and in the putty manufacturing step, the components constituting the elastic putty composition described above are sequentially added to and mixed with the resin composition.
[0080] At this time, mixing is performed at a rotational speed of about 750 rpm to 900 rpm, and these high-speed stirring conditions are intended to ensure that each component is uniformly dispersed even in systems with high solid content, thereby simultaneously securing the physical properties and workability of the putty.
[0081] In particular, inorganic fillers such as calcium carbonate and diatomaceous earth tend to aggregate easily, so mixing conditions that provide sufficient shear force are required.
[0082] After mixing is complete, a vacuum degassing process is performed to remove microbubbles that may be contained in the composition.
[0083] This process plays an important role in preventing defects such as pinholes or pores during film formation and in improving the density and mechanical strength of the film.
[0084] In addition, a uniform composition with air bubbles removed forms a smoother surface during application, which can significantly improve the appearance quality when applying a topcoat.
[0085] Consequently, the elastic putty composition of the present invention, manufactured through the stepwise process described above, can be provided as a high-performance, eco-friendly putty highly suitable for repairing cracks in concrete structures by forming a dense film structure with uniform particle distribution and bubble-free air bubbles, along with excellent durability based on a self-curing resin structure.
[0086] The following describes the embodiments.
[0087] [Example 1]
[0088] A self-curing acrylic emulsion resin composition was prepared as shown in Table 1 below.
[0089]
[0090] At this time, the physical properties of this composition were a solid content of 61%, a viscosity of 2900-3100 cps (25℃), and a Tg of -23℃ to -25℃.
[0091] [Example 2]
[0092] As shown in Table 2 below, elastic putty was prepared.
[0093]
[0094] For comparison, as a comparative example, other components were made the same as in [Example 2], but without including diatomaceous earth and DOA.
[0095] Then, the mechanical properties of the elastic putty of Example 2 and the elastic putty of the comparative example were evaluated according to KS F 3211.
[0096] As a result of the evaluation, the elastic putty of the present invention achieved an elongation of 220%, a tensile strength of 2.8 MPa, and an adhesion of 1.5 MPa, whereas the comparative example showed a significant difference with an elongation of 140%, a tensile strength of 1.9 MPa, and an adhesion of 1.2 MPa.
[0097] In addition, low-temperature flexibility was evaluated under bending test conditions after maintaining -10℃ for 24 hours.
[0098] As a result of the evaluation, the elastic putty of the present invention did not develop cracks, whereas the comparative example developed cracks.
[0099] Accordingly, it was confirmed that the embodiment of the present invention containing DOA maintained flexibility even at low temperatures, whereas the comparative example developed cracks due to increased brittleness.
[0100] In addition, the appearance of the topcoat was evaluated visually after the water-based paint application.
[0101] As a result of the evaluation, the elastic putty of the present invention was excellent in terms of gloss uniformity and the occurrence of stains, showing no stains, whereas the comparative example caused problems of poor gloss and stains.
[0102] In addition, storage stability was evaluated under test conditions of 25℃ and 30 days of storage.
[0103] As a result of the evaluation, the present invention did not experience changes in viscosity or precipitation, whereas the comparative example caused problems such as increased viscosity and precipitation.
[0104] Through this, it was confirmed that the present invention maintains a stable dispersion state.
[0105] According to another embodiment of the present invention, the diatomite may include a first diatomite and a second diatomite having different average particle sizes.
[0106] The first diatomite may be fine diatomite with an average particle size of 5㎛ to 30㎛, and the second diatomite may be coarse diatomite with an average particle size of 35㎛ to 90㎛.
[0107] The first diatomite above plays a role in improving the density and surface smoothness of the coating film by filling the fine pores between calcium carbonate and pigments within the elastic putty composition.
[0108] The above-mentioned second diatomite forms a fine irregular structure on the surface of the coating film, thereby reducing specular reflection of light and inducing diffuse reflection after topcoat application, and thus suppresses the phenomenon in which the repair area appears stain-like due to differences in gloss.
[0109] The first diatomite and the second diatomite may be included in a weight ratio in the range of 7:3 to 3:7, and more preferably in the range of 6:4 to 4:6.
[0110] In addition, the above diatomaceous earth is not added all at once during the putty manufacturing process; 40% to 70% by weight of the total diatomaceous earth is added first in a primary mixing step containing an acrylic emulsion resin composition, water, and a dispersant, and the remaining 30% to 60% by weight can be added in a later mixing step after adding a hydrophobic modified urethane-based thickener.
[0111] In this way, by using diatomaceous earth with different particle sizes in combination and adding them in stages, excessive aggregation of the diatomaceous earth within the composition is suppressed, and the filling properties inside the film and the matte finish of the film surface can be secured in balance.
[0112] As a result, even if water-based paint or an exterior topcoat is applied after applying elastic putty to the repaired concrete cracks, the difference in gloss between the repaired and non-repaired areas is further reduced, effectively suppressing the occurrence of stains.
[0113] According to another embodiment of the present invention, the elastic putty composition may further include elastic hollow microparticles and microfibers to improve conformability to repeated crack expansion and shrinkage.
[0114] The above elastic hollow microparticles may be one or more of acrylic hollow microparticles, styrene-acrylic hollow microparticles, or urethane hollow microparticles.
[0115] The above elastic hollow microparticles may be included in an amount of 0.3 to 3.0 parts by weight per 100 parts by weight of the elastic putty composition.
[0116] The above elastic hollow microparticles form a fine buffer space within the coating film, serving to disperse the stress concentrated in the film even if the crack width repeatedly changes due to drying shrinkage of the concrete structure, temperature changes, or external vibrations.
[0117] In addition, the microfibers may be one or more of cellulose fibers, polypropylene fibers, polyethylene fibers, or polyester fibers.
[0118] The above microfibers may have an average length of 0.1 mm to 3.0 mm and may be included in an amount of 0.05 to 1.0 parts by weight per 100 parts by weight of the elastic putty composition.
[0119] The above microfibers form a fine reinforcing network within the coating film, thereby preventing the film from tearing abruptly at a specific point when tensile force is applied to the crack repair area, and dispersing stress around the crack.
[0120] In this way, by including elastic hollow microparticles and microfibers together, the elastic putty composition can not only secure elongation but also secure resilience against repeated deformation, tear resistance, and long-term crack-following ability.
[0121] Therefore, the elastic putty composition according to the present embodiment is particularly suitable for repairing microcracks in concrete of exterior walls, rooftop parapets, underground parking lot walls, window frames, and bridge substructures where seasonal temperature changes are significant.
[0122] According to another embodiment of the present invention, the elastic putty composition may further include a composite adhesion promoter to improve initial adhesion to wet concrete or an alkaline inorganic substrate.
[0123] The above composite adhesion promoter may include epoxysilane and aminosilane.
[0124] The above epoxysilane may be one or more of γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropylmethyldiethoxysilane, or 3-glycidoxypropyltriethoxysilane.
[0125] The above aminosilane may be one or more of 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, or N-2-aminoethyl-3-aminopropyltrimethoxysilane.
[0126] The above composite adhesion promoter may be included in an amount of 0.1 to 2.0 parts by weight per 100 parts by weight of the elastic putty composition.
[0127] In addition, the epoxysilane and aminosilane may be included in a weight ratio in the range of 8:2 to 2:8.
[0128] The above epoxysilane plays a role in improving interfacial bonding between the acrylic emulsion resin composition, diatomaceous earth, and calcium carbonate, and the above aminosilane plays a role in improving initial adhesion by interacting with hydroxyl groups or alkaline surfaces present on the surface of concrete, mortar, and cementitious substrates.
[0129] In particular, crack repair work on concrete structures is difficult to perform only when the surface is completely dry, and trace amounts of moisture often remain on the substrate surface in basements, exterior walls, rooftops, and areas with signs of leakage.
[0130] When a composite adhesion promoter is included as in the present embodiment, the elastic putty composition can be stably adhered to the substrate even if a small amount of moisture is present on the substrate surface, and lifting, peeling, and edge curling of the coating film after drying can be suppressed.
[0131] In addition, the above composite adhesion promoter can also interact with the surface of inorganic fillers such as diatomaceous earth and calcium carbonate, thereby improving interfacial bonding between the inorganic components inside the coating film and the acrylic resin, and as a result, long-term water resistance and adhesion stability can be improved.
Claims
Claim 1 It comprises 1.0–2.0 wt% diacetone acrylamide, 15–20 wt% n-butyl acrylate, 0.5–1.5 wt% methacrylic acid, 1.0–2.2 wt% acrylonitrile, 13–18 wt% butyl methacrylate, 13.2–17.5 wt% 2-ethylhexyl acrylate, 2.2–3.0 wt% styrene, 0.5–2.0 wt% adipic acid dihydrazide, 0.07–0.2 wt% ammonium peroxide, 0.06–2.2 wt% ammonium persulfate, 0.1–0.5 wt% ammonium hydroxide, 0.25–0.75 wt% nonionic emulsifier, and the remainder being ion-exchanged water, wherein by the reaction between the diacetone acrylamide and the adipic acid dihydrazide A self-curing eco-friendly acrylic emulsion resin composition having a self-crosslinking structure, a solid content of 60% by weight or more, a viscosity of 2900-3100 cps (25°C), and a glass transition temperature (Tg) of -23°C to -25°C; wherein, based on 100 parts by weight of the self-curing eco-friendly acrylic emulsion resin composition, 5.5 parts by weight of 2-(acetoacetoxy)ethyl methacrylate, 5 parts by weight of trimethylolpropane tris(2-methyl-1-aziridinepropionate), and 4.5 parts by weight of perfluoropolyether methacrylate are further added. Claim 2 A self-curing eco-friendly acrylic emulsion resin composition according to claim 1, characterized in that the nonionic emulsifier is an alcohol ethoxylate. Claim 3 A method for manufacturing a self-curing eco-friendly acrylic emulsion resin composition according to claim 1 or 2, comprising: (a) a step of introducing an initiator into an aqueous reaction system containing ion-exchanged water and a nonionic emulsifier and initiating a reaction at 70 to 90°C; (b) a step of copolymerizing by drop-introducing a monomer mixture for 3 to 4 hours; (c) a step of performing secondary polymerization by introducing an additional initiator and removing unreacted monomers under vacuum; and (d) a step of stabilizing the emulsion by cooling the reaction mixture to 40 to 50°C and adjusting the pH. Claim 4 A self-curing acrylic emulsion resin composition according to claim 1 or 2 comprising 55-65 wt%, sodium hexametaphosphate 0.1-0.3 wt%, water 4.0-8.5 wt%, 1,2-benzisothiazolin-3-one 0.2-0.5 wt%, TiO₂ 0.5-3.0 wt%, hydroxyethyl cellulose 0.5-1.3 wt%, pigment 1-6 wt%, polydimethylsiloxane 0.1-0.3 wt%, DOA 1-2 wt%, Texanol 1.5-3.0 wt%, diatomaceous earth 10-15 wt%, hydrophobic modified urethane-based thickener 0.1-1.0 wt%, and the remainder being calcium carbonate, wherein the gloss of the coating film is reduced by the diatomaceous earth, thereby suppressing the occurrence of stains during topcoat application, and the above In an elastic putty composition in which elongation is maintained even in a low-temperature environment by means of DOA (dioctyl adipate); wherein the diatomite is composed of a first diatomite and a second diatomite having different average particle sizes, wherein the first diatomite is fine diatomite with an average particle size of 5 μm to 30 μm, and the second diatomite is coarse diatomite with an average particle size of 35 μm to 90 μm, and the first diatomite and the second diatomite are included in a weight ratio in the range of 6:4 to 4:6; and wherein, for 100 parts by weight of the elastic putty composition, γ-glycidoxypropyltrimethoxysilane An elastic putty composition characterized by further adding 8.5 parts by weight of polyetheramine, 3.5 parts by weight of polyetheramine, and 5 parts by weight of dimethylaminoethyl methacrylate.
Citation Information
Patent Citations
Eco-Friendly Surface-Protection Coating Composition and Protecting and Repairing Methods of Concrete Structure Using Thereof
KR101937454B1
Water-proofing putty composition containing environment affinity type water dispersable poly-acryl urethane emulsion, preparing method thereof and putty coating method using the same
KR1020190030917A
Water-proofing putty composition and putty coating method using the same
KR102025182B1
Eco-friendly biobased aqueous paint
KR102543803B1
Water-based resin dispersion, top coat coating, and manufacturing method therefor and coated film
JP2019189709A
